(untitled) (Revista científica Olimpia, 2020)
In the following work it is approached as the baloncestistas that occupy the position of defenses they reached the values of the absolute force in the musculature extensoras of the arms, trunk and legs, to the beginning and final of the general stage, the same ones got ready to participate in the National Tournament of Ascent of the Basketball Cuban masculine sex belonging to the oriental area of the 2017-2018. To carry out the valuation of the results we lean on in the statistical package SPSS 0.20, the one that facilitated the analysis of the values averages for muscular planes through the descriptive statistic. The results reached by this baloncestista group belonged together with the training of the proposed force.